Superparamagnetic nanoparticles – a tool for early diagnostics (Swiss Medical Weekly, 2010)
Nanoparticles show several interesting new physical and biological properties and therefore play an increasing role in pharmaceutics and medicine. For more than 30 years this research field has been developing slowly but steadily from physical and biological interest (bench) to applications in clinics (bedside). However, many of these particles for biomedical applications are still in the pre-clinical or clinical phase. Combined with drugs or genes these nanoparticles may change the viability of or the transcription processes in cells, which make them interesting for the pharmaceutical industry, cell biology and diagnostics. Because most of the application of superparamagnetic nanoparticles as therapeutic tool, like non-viral vector, drug delivery, are still far from clinical use, this review will concentrate on superparamagnetic nanoparticles as versatile agent for early diagnosis, including the use of such particles as contrast agent for MR imaging and as vehicle for the detection of biomarkers.